Profile of the Needs of Sriwijaya University Physics Education Students Against the Solar Observation Module - Hamdi Akhsan; Sri Mindia Vanessa Pratiwi; Melly Ariska (Program Studi Pendidikan Fisika FKIP Universitas Riau, 2023)
The research aimed to find out the needs of the Physics Education Study Program students for the observation module that needs to be developed for the IPBA course at FKIP Universitas Sriwijaya (UNSRI). The initial needs analysis for the sun observation module refers to Rowntree's research model. The research was conducted using a survey method of students of the Physics Education Study Program. The research instrument used a questionnaire consisting of 6 question items about IPBA learning on celestial bodies. Data collection uses the survey method provided via Google Forms. Data analysis was carried out based on the results of filling out the questionnaire by respondents which were displayed in percentage form. The results of the analysis of the needs for the development of the observation module gave the result that students as a whole agreed to develop the module as a support in the IPBA learning process for celestial bodies without practicum on the topic of the sun so that the concept is easier to understand.